Attitudes of physics teachers towards teaching through educational platforms and programs Social Media (Journal of the College of Basic Education, 2022)
The research aims to identify the attitudes of physics teachers in Qadisiyah Governorate towards teaching through educational platforms and social media programs. The researcher used the descriptive research because it is appropriate for this study. The research community consisted of physics teachers in the General Directorate of Education of Qadisiyah, who numbered 243 teachers, who chose 110 teachers randomly. The questionnaire consisted of 55 items according to four domains (the first domain was the experience of physics teachers in e-learning, the second domain was academic content, the third domain was student responses, and the fourth domain was teaching methods) The validity and stability of the scale were confirmed. The researcher used the spss statistical bag to analyze the results and calculate the stability by using the alpha Krupach equation. The researcher concluded that there are negative trends for physics teachers towards electronic teaching through educational platforms because they believe that traditional education face to face with the student is better because they believe that it does not support social aspects and that regular teaching More effective than electronic teaching via communication platforms because it shortens time and effort. The researcher recommended a number of recommendations and suggestions